A Comparison between Solving of Two-Dimensional Nonlinear Fredholm Integral Equations of the Second Kind by the Optimal Homotopy Asymptotic Method and Homotopy Perturbation Method - ALMOUSA, Mohammad; ISMAIL, Ahmad (Walailak Journal of Science and Technology (WJST), 2014)
In this article, we present the optimal homotopy asymptotic method (OHAM) and homotopy perturbation method (HPM) for solving 2-dimensional nonlinear Fredholm integral equations of the second kind. A comparison is made between these methods to solve 2-dimensional nonlinear Fredholm integral equations of the second kind. The results show that the presented methods are very powerful and simple techniques in solving 2-dimensional nonlinear Fredholm integral equations of the second kind. doi:10.14456/WJST.2015.35